Percutaneous treatment of late complications of the Bentall procedure. Issue 2 (15th March 2017) - Delorme, S.; Ruchat, P.; Goy, J.J.
Abstract : Aortic pseudo‐aneurysm following the Bentall procedure is a rare but potentially severe complication. Surgical reintervention represents a high risk. We report on two cases with different pseudo‐aneurysm types which were successfully treated using two different percutaneous techniques. © 2017 Wiley Periodicals, Inc.